Discovery of 6-phenylimidazo[2, 1-b]thiazole derivatives as a new type of FLT3 inhibitors. Issue 20 (15th October 2015) - Lin, Xing-Dong; Yang, Hui-Wen; Ma, Shuang; Li, Wei-Wei; Zhang, Chun-Hui; Wang, Wen-Jing; Xiang, Rong; Li, Lin-Li; Yang, Sheng-Yong
Graphical abstract